Pemetaan Tingkat Kompetensi Sumber Daya Manusia di Hotel Grand Tamaro Parapat - Butarbutar, Ridolli (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
This study aims to map the competency levels of human resources (HR) at Hotel Grand Tamaro Parapat, focusing on three key dimensions: knowledge, skills, and attitude. The research is motivated by the critical importance of service quality in the hospitality industry, which relies heavily on the capability of its human resources. A qualitative approach was employed, utilizing data collection techniques such as observation, in-depth interviews, and documentation. Data were analyzed using a quadrant-based framework to categorize employees into four groups according to the combination of their knowledge, skills, and attitude. The findings reveal a significant competency gap across several departments, particularly in the dimensions of attitude and skills. The study recommends the implementation of regular training programs, professional certification schemes, and the cultivation of a supportive work culture as strategic efforts to sustainably enhance HR competencies.